LOWERING AFFECTIVE FILTERS IN SPEAKING (American Journal of Interdisciplinary Research and Development, 2023)
In the process of learning a language, naturally, most learners encounter language barriers, which serve as a general term for "affective filters". The main goal of the research work is to study the influence of affective filters, in particular motivation, attitudes, self-confidence and language anxiety. This article also aims to study the factors that reduce the performance of first-year students and offer the most appropriate solutions by questioning and analyzing their oral responses.